Casimir en Einstein. ‘Hij kan al wat maar heeft nog slaag nodig’ - van Delft, Dirk (Studium, 2016)
Casimir and Einstein Hendrik Casimir knew Albert Einstein from the presentations he gave at Paul Ehrenfest’s Leiden colloquiums in the late 1920s. As a student he witnessed Einstein’s determined opposition to quantum mechanics, expressed in sharp thought experiments. After Ehrenfest’s suicide they lost touch. Their scientific work, however, still proved to have a connection long after Einstein’s death. Einstein’s last great discovery of the Bose Einstein condensation of 1924 and the Casimir effect due to vacuum fluctuations of 1948 converge in modern physics research.